A boundary integral equations method for asymmetric Stokes fiow between two parallel planes - Kohr, M. (Archives of Mechanics, 1997)
In this paper we apply a direct boundary integral equations method to Stokes flow past a smooth obstacle, occurring between two parallel planes. The problem is formulated exactly as a system of linear Fredholm integral equations of the second kind, over the surface of the obstacle. It is shown that this system has a unique continuous solution when the boundary of the particle is a Lyapunov surface and the velocity distributions on the same boundary is continuous. The numerical results are obtained by a standard boundary element method.